Al-Nuṣūṣ al-Qadīmah wa al-Baḥth al-Tārikhī al-Ijtimā’ī fī al-Fikri al-Islāmī bi Indūnīsīyā - Tjandrasasmita, Uka (Studia Islamika, 2002)
This article aims to highlight the importance of these manuscripts, which have a religious flavor, in relation to writings on the socio-intellectual history of Islam in Indonesia. According to this writer, these manuscripts contain much information and important knowledge, all of which may be beneficial to the reconstruction of several trains of Islamic intellectual thought, particularly Sufi thought, which of course heavily influenced the nature of early Islam in Indonesia. Unfortunately, to date, studies related to this history of Islam in Indonesia have often neglected to use these manuscripts as a primary source. Further, in the context of local Islam, the manuscripts are an important source, and ought to be used as a reference.DOI: 10.15408/sdi.v9i2.669